Cassava genetic resources: a global approach for conservation and use - Iglesias, C.A.; Iwanaga, Masaru (International Center for Tropical Agriculture, 1993)
An international workshop on cassava genetic resources was recently held at CIAT. The main objectives of the meeting were to assess the present status of cassava germplasm conservation and use, and to examine the possibility of establishing a global network for cassava genetic resources. A global conservation strategy was discussed, based on the present status of national and international cassava genetic resources programs. Priorities were set for future germplasm collecting expeditions and sharing of conservation workload among institutions for both cassava and wild Manihot germplasm. The discussion on a global strategy for conservation of genetic resources involved areas such as: studies on genetic diversity, definition of core collections, identification of duplicate accessions, in-vitro and cryopreservation techniques, duplication of germplasm collections in other institutions, sexual seed and pollen gene collections, etc. The existing mechanisms for safe germplasm exchange were evaluated for an effective movement of genetic resources within the network. Other important subjects discussed during the meeting were: the development of data bases for cassava germplasm, human resource development, and the integration of the germplasm network with other networks (i.e. CBN) and its implications.